2020
DOI: 10.1016/j.jenvman.2019.109722
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and evaluation of urban soundscapes worthy of preservation

Abstract: Improvement of the sound environment is essential for improving the overall quality of the urban environment and for reflecting the characteristics of a city. Unfortunately, some soundscapes in cities are gradually being destroyed by the rapid development. Therefore, it would appear that the preservation of soundscapes is as necessary and crucial as noise control in cities. In this paper, two field studies were carried out at two stages to explore the types and characteristics of urban soundscapes that should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 48 publications
3
21
0
1
Order By: Relevance
“…It appears that each of the four different activities needs particular sound sources. This finding is consistent with the result from Jia, et al [20], who showed that the dominant characteristic of a place is determined by a combination of certain sounds rather than a dominant sound. The sound source selections in the acoustic environment compositions for the activity of reading are shown in Figure 7.…”
Section: Sound Source Selection Of Acoustic Environment Composition B...supporting
confidence: 93%
See 1 more Smart Citation
“…It appears that each of the four different activities needs particular sound sources. This finding is consistent with the result from Jia, et al [20], who showed that the dominant characteristic of a place is determined by a combination of certain sounds rather than a dominant sound. The sound source selections in the acoustic environment compositions for the activity of reading are shown in Figure 7.…”
Section: Sound Source Selection Of Acoustic Environment Composition B...supporting
confidence: 93%
“…Some sound sources from people's activities are also not preferred in spaces for relaxing activities. A previous study conducted by Jia, et al [20] showed that communal sounds related to talking, laughter, and other sounds from human activities are related to social activities. The sound of children playing has a more significant relationship with people not engaged in relaxing than the sound of people talking.…”
Section: Sound Source Selection Of Acoustic Environment Composition B...mentioning
confidence: 98%
“…The study proves that people spending time in the Jakubowo Park recognize the area of the eastern part of the park bordering on Wojska Polskiego St. as the noisiest and most unpleasant. The western and central parts of the park proved to be the highest rated area in terms of sound quality (points 23,33,34,38,40). Positive rating was given to areas around water reservoirs (points 40-42).…”
Section: Test II Interview With Park Users In the Jakubowo Parkmentioning
confidence: 99%
“… 33 Therefore, preservation 34 and improvement of the noise environment are considered essential means to improve the quality of the urban environment and reflect the city’s characteristics. 35 , 36 …”
Section: Introductionmentioning
confidence: 99%